Hypertensive Rats Treated Chronically With Nω-Nitro-L-Arginine Methyl Ester (L-NAME) Induced Disorder of Hepatic Fatty Acid Metabolism and Intestinal Pathophysiology - Li, Bo; He, Xinglishang; Lei, Shan-Shan; Zhou, Fu-Chen; Zhang, Ning-Yu; Chen, Ye-Hui; Wang, Yu-Zhi; Su, Jie; Yu, Jing-Jing; Li, Lin-Zi; Zheng, Xiang; Luo, Rong; et al. (Frontiers in Pharmacology, 2020)
Nω-nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide (NO) biosynthesis, results in hypertension and liver injury. This study aimed at investigating the changes of liver lipometabonomics and exploring the underlying mechanisms of liver injury in the L-NAME-treated rats. The male Sprague-Dawley (SD) rats were treated with L-NAME (40 mg/kg, p.o.) for eight weeks. After that, the liver, aorta, fecal, and serum were collected for analysis. The results showed that L-NAME induced hypertension and disordered the endothelial nitric oxide synthase (eNOS)-NO pathway in the treated rats. L-NAME could also increase the levels of serum total cholesterol (TC), triglyceride (TG), alanine transaminase (ALT), and aspartate transaminase (AST). The multidimensional mass spectrometry-based shotgun lipidomics (MDMS-SL) analysis showed that L-NAME could induce significant changes of the total hepatic lipids and most hepatic triglycerides, as well as fatty acid. A positive correlation was found between the blood pressure and TAG. Immunofluorescence and Western-Blot experiments indicated that the L-NAME treatment significantly influenced some FA β-oxidation, desaturation, and synthesis-related proteins. The increase of intestinal inflammation, decrease of microcirculation and tight junction proteins, as well as alterations of microbial communities were observed in the L-NAME induced hypertensive rats, as well as alterations of microbial communities were notable correlation to TAG and FA species. This study demonstrated that the L-NAME-induced hypertensive rats exhibiting liver injury were the joint action of hepatic abnormal fatty acid metabolism and microcirculation disorder. Furthermore, the gut microflora, as well as the changes of FA β-oxidation (ACOX, CPT1α), desaturation (SCD-1), and synthesis (FAS) may be the potential mechanisms for abnormal fatty acid metabolism.